2015
DOI: 10.5858/arpa.2013-0520-rs
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Manifestations of von Hippel–Lindau Disease

Abstract: von Hippel-Lindau (VHL) disease is an autosomal dominant disorder caused by heterozygous mutations in the VHL tumor suppressor gene that is characterized by the occurrence of multiple endocrine and nonendocrine lesions. This review focuses on the endocrine manifestations of VHL disease. Pancreatic neuroendocrine proliferations (ductuloinsular complexes, islet dysplasia, endocrine microadenoma, and neuroendocrine tumors), pheochromocytomas, and extra-adrenal paragangliomas are important endocrine manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
0
43
0
4
Order By: Relevance
“…However, these tumors differ in their molecular and immunohistochemical profiles [23]. In addition, VHL disease may present with endocrine manifestations including pheochromocytomas, extra-adrenal paragangliomas, and pancreatic neuroendocrine tumors [24]. Though VHL syndrome was a consideration with the constellation of findings described in this case, this was effectively ruled out through immunohistochemistry and genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, these tumors differ in their molecular and immunohistochemical profiles [23]. In addition, VHL disease may present with endocrine manifestations including pheochromocytomas, extra-adrenal paragangliomas, and pancreatic neuroendocrine tumors [24]. Though VHL syndrome was a consideration with the constellation of findings described in this case, this was effectively ruled out through immunohistochemistry and genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations cause the so-called VHL disease, an autosomal dominant disorder characterized by retinal angioma, cerebellar and spinal hemangioblastomas, clear-cell renal cell carcinoma (ccRCC), pheochromocytoma and pancreatic neuroendocrine tumor (Maher et al 2011). Besides, a number of sporadic cancers, including ccRCC, are strongly associated with VHL reduced expression and/or loss-of-function mutations (Gnarra et al 1994;Cassol and Mete, 2015). The best characterized pVHL function is ubiquitination followed by proteasome degradation of target proteins (Robinson and Ohh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has even been proposed that the two entities are indeed the same, with clear cell NET representing the coalescence of multiple small lipid vacuoles into one large vacuole, which clears out the cytoplasm of the cell. 3,11 Singh et al studied 11 pancreatic NETs with foamy, microvesicular cytoplasm, and confirmed in three cases, by electron microscopy, that the cytoplasmic vesicles were lipid vacuoles. Only one of the eleven cases involved a patient who had VHL.…”
Section: Discussionmentioning
confidence: 91%
“…However, we will continue to use the term clear cell NET to refer to both clear cell NET and lipid‐rich NET, as they seem to be used interchangeably in most studies, and there does not appear to be sufficient evidence to separate them. It has even been proposed that the two entities are indeed the same, with clear cell NET representing the coalescence of multiple small lipid vacuoles into one large vacuole, which clears out the cytoplasm of the cell …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation